Endoscopic Transcaruncular Medial Orbitotomy as an Alternative Approach to Anterior Ethmoidal Artery Coagulation - Matoušek, Petr; Čábalová, Lenka; Masárová, Michaela; Komínek, Pavel (The Journal of craniofacial surgery, 2019)
BACKGROUND: The authors present a series of 5 patients with anterior epistaxis in which a transcaruncular endoscopic approach was used for the anterior ethmoidal artery coagulation (AEA). METHODS: Six AEA coagulations (5 unilateral, 1 bilateral) using the transcaruncular endoscopic approach were performed in 5 patients with anterior epistaxis resistant to conservative measures. An incision was made between the plica semilunaris of conjunctiva and the lacrimal caruncle. Using a rigid endoscope, tissues were dissected lateral to the lacrimal sac, to the posterior lacrimal crest. The periorbit was incised and pulled aside. Hereafter, the technique was the same as that involving a frontoethmoidal incision. After bipolar coagulation of the AEA, the conjunctiva was sutured. RESULTS: Bleeding was resolved in all patients. One patient experienced early postoperative temporary diplopia. CONCLUSIONS: The transcaruncular endoscopic approach is a promising technique with no outer scarring. It is convenient in patients with difficult orientation in the nasal cavity, relatively safe, and faster than the transnasal endoscopic approach.
Keywords: Conjunctiva; dospělí; elektrokoagulace; Epistaxis; Female; Nasal Cavity; Adult; epistaxe; nosní dutina; ženské pohlaví; lidé; orbita; Electrocoagulation; konjunktiva; Arteries; Male; Aged; lidé středního věku; senioři; mužské pohlaví; Hemostasis, Endoscopic; Middle Aged; Orbit; arterie; hemostáza endoskopická; Humans